Avaliação agronômica de espécies para adubação verde e sua influência em atributos químicos e físicos do solo. - Ferreira, Núbia Marisa (2017)
Green fertilization is an important agricultural practice used in several regions of Brazil. This practice can be used to improve soil chemical (e.g soil pH, soil organic matter, and soil fertility) and soil physical (e.g. soil density and soil porosity) properties due to its role on soil conservation and maintenance of soil fertility. However, in the brazilian Northeast, there are few works with green fertilization, emphasizing the importance of evaluating the cover crops performance into this region. Our objective with this experiment was to evaluate the agronomic characteristics, nutritional status and influence of different cover crops used as green fertilizers on the chemical and physical properties of the soil. For this purpose, a field experiment was carried out in a randomized complete block design, with nine treatments, and three blocks. The treatments were: Canavalia ensiformes (L.) DC., Crotalaria spectabilis Roth, Crotalaria ochroleuca G. Don., Crotalaria juncea L., Dolichos lablab L., Stizolobium niveum (Roxb.) Kuntze, Stizolobium aterrimum Piper & Tracy, Neonotonia wightii (Wight & Arn.) J.A. Lackey and Pennisetum glaucum (L.) R.Br.. We evaluated the plant growth, cover rate, green and dry biomass, content and nutrient accumulation in the plant tissue, rate of decomposition and the chemical and physical attributes of the soil. The database was submitted to one-way ANOVA and Tukey's post-hoc test. For the decomposition rate, we used the exponential model Mt = M0 * e kt to analyse it. We found that C. ochroleuca e C. ensiformes were more precocious and present higher growth than other studied cover crops. N. wightii, S. niveum e S. aterrimum showed higher premature cover rates. For the plant nutritional status, we found higher N content in C. ensiformes and C. spectabilis; higher P, K and S in P. glaucum; and finally higher Mg content in C. ochroleuca. We also found higher decomposition rate in C. spectabilis. For soil properties (chemical and physical) we observed that the cover crops influence significantly the studied parameters in the soil surface. P. glaucum, C. ochroleuca, C. ensiformes and N. wightii showed higher organic matter content, K cycling, and sum of bases, while S. aterrimum and S. niveum promotes higher soil density and soil porosity.